PENERAPAN MODEL THINK PAIR SHARE UNTUK MENINGKATKAN KETERAMPILAN BERBICARA KELAS IV SDN 110 PINRANG - Ilmi, Nur; Muksin, Ika; Yulia (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
This research was motivated by the low quality of the learning process and speaking skills of fourth-grade students at UPT SD Negeri 110 Pinrang. The study aimed to examine how the implementation of the Think Pair Share learning model could enhance the quality of classroom learning and students' speaking skills. A qualitative approach was employed, specifically using Classroom Action Research (CAR). The research subjects included one teacher and 18 fourth-grade students at UPT SD Negeri 110 Pinrang. Data collection methods involved observation and documentation, which were analyzed through data condensation, data presentation, and conclusion drawing. The research was conducted over two cycles. The findings revealed that in both the first and second cycles, the teacher's instructional activities were categorized as good (B). Meanwhile, student activities, which were initially rated as sufficient (C) in the first cycle, improved to the good category (B) in the second cycle. This improvement was also reflected in the students' speaking skills, which increased from the sufficient category (C) in the first cycle to the good category (B) in the second cycle. Based on these results, it can be concluded that the Think Pair Share learning model is effective in enhancing both the quality of the learning process and the speaking skills of fourth-grade students at UPT SD Negeri 110 Pinrang